Evaluasi Usability Pada Aplikasi Nutribid Menggunakan Usability Testing - Muhamad Iqbal Faddillah; Intan Purnamasari; Oman Komarudin (Peneliti.net, 2022)
The health and nutrition of pregnant women can affect the growth of the fetus and pose a risk of stunting. Other factors are the mother's posture (short), the distance between pregnancies, the young age of the mother, lack of nutritional intake during pregnancy. One application that provides nutritional consulting services is Nutribid. Usability can be used as a measure of the success of a system in achieving the goals of the system by paying attention to the needs of testing users. The purpose of designing and evaluating a product or service for usability is to achieve effectiveness, efficiency and satisfaction based on the user's point of view. To obtain these three aspects, the researchers used usability testing and a user experience questionnaire. The use of usability testing is carried out to obtain aspects of effectiveness and efficiency, while the use of a user experience questionnaire is carried out to obtain aspects of efficiency and user satisfaction. After conducting usability testing and user experience questionnaires, six usability problems have been collected, namely, adding clarity to the information provided in the health calculator section of daily energy needs by changing the word